2015
DOI: 10.1504/ijsom.2015.069656
|View full text |Cite
|
Sign up to set email alerts
|

The influence of SERVQUAL dimensions on customer loyalty in banking sector, India - an empirical study

Abstract: Banking sector offers excellent service to customers in order to sustain in the competitive business environment. Customer satisfaction that leads to customer loyalty is the backbone of any bank. Hence, an empirical study was conducted with main focus on the various dimensions of service quality (SERVQUAL) of a Scheduled Bank that ultimately leads to customer loyalty. Data was collected through a survey research from 250 customers of five district bank branches, 50 from each branch in Tamil Nadu, India. From t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…Moreover, empathy was found to be a significant predictor of customer satisfaction in the banking sector along with other service quality variables (Al Karim, 2019;Ali and Raza, 2017;Dawit and Mesfin, 2019;Gajewska et al, 2019;Janahi and Al Mubarak, 2017;Kant and Jaiswal, 2017;Singh, 2020;Titko and Lace, 2010;Vasumathi and Subashini, 2015). Amidst the studies, Tien et al (2021) identified that empathy has highest impact on the satisfaction of customers in the commercial banks in Vietnam.…”
Section: Competency and Customer Satisfactionmentioning
confidence: 95%
“…Moreover, empathy was found to be a significant predictor of customer satisfaction in the banking sector along with other service quality variables (Al Karim, 2019;Ali and Raza, 2017;Dawit and Mesfin, 2019;Gajewska et al, 2019;Janahi and Al Mubarak, 2017;Kant and Jaiswal, 2017;Singh, 2020;Titko and Lace, 2010;Vasumathi and Subashini, 2015). Amidst the studies, Tien et al (2021) identified that empathy has highest impact on the satisfaction of customers in the commercial banks in Vietnam.…”
Section: Competency and Customer Satisfactionmentioning
confidence: 95%
“…When the service to the customer is exceptional, the customers become satisfied with the service (Lai & Cheng 2016;Shanka 2012;Vasumathi & Subashini 2015). For the purposes of this article, customer satisfaction is defined as the complete fulfilment of customer expectations (Ali & Raza 2017).…”
Section: Literature Reviewmentioning
confidence: 99%
“…To authors such as Yannis et al 2014, satisfaction appears to be a new way for improving logistics service quality of some firms. Delivering right service quality leads to consumer satisfaction and ultimately consumer loyalty (Vasumathi & Subashini, 2015;Kabiraj & Uniyal, 2013). Consumer satisfaction with service quality is a competitive advantage for the service industry (Hsieh & Yeh, 2015).…”
Section: Satisfaction As a Mediator In Crm And CL Linkmentioning
confidence: 99%